Measurement of singlet delta oxygen in an atmospheric-pressure helium-oxygen plasma jet - Inoue, Yuki; Ono, Ryo (Journal of physics. D, Applied physics, 2017)
The density of singlet delta oxygen O2(a1Δg) is measured in situ in a He/O2 atmospheric-pressure plasma jet using optical emission spectroscopy at 1.27 μm. A sinusoidal high voltage of 1-10 kHz is applied between two electrodes wrapped around a quartz tube, in which the working gas flows. The two-dimensional distribution of the O2(a1Δg) density shows that O2(a1Δg) is primarily produced in the dielectric barrier discharge inside the quartz tube and that the O2(a1Δg) production in the plasma jet plume is negligibly small. Typically, 100 ppm of O2(a1Δg) is produced. The O2(a1Δg) density increases with O2 concentration and is proportional to the specific input energy (SIE; J/l) irrespective of the discharge voltage, frequency, and gas flow rate. The O2(a1Δg) production per SIE was 10 ppm/(J/l). The loss processes of O2(a1Δg) via reactions with O3 and O2 are discussed. The O2(a1Δg) density decreases when the working gas is humidified. An addition of 200 ppm of H2O decreases the O2(a1Δg) density by half.